ANXIETY AMONG THE URBAN WORKING WOMEN AND HOMEMAKERS: A QUESTIONNAIRE-BASED SURVEY - JANA, NIKTA; NAYAKA, MONIKA; DEVERSHETTY, SHRAVANI; GAJJALA, PRAVEEN KUMAR; KAMDAR, PRIYANKA; PAL, CHANDANA (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: Increasing complexity of life is associated with a parallel increase in anxiety, particularly among women due to their physiology and hormonal influence. This study evaluated and compared the anxiety status of working women and homemakers. Methods: The target population for this survey-based study were selected randomly; responses for the questionnaire was assessed and scoring was done with the help of a scoring key. PSYCOM anxiety test was used for the assessment of anxiety. Results: Sixty women (30 in each groups) participated in the survey; anxiety was common among those in the age group of 21−40 years. Twenty-two (36.66%) had no symptoms of anxiety, of whom 13 (59.01%) were working women. Anxiety levels were high among home makers (70% vs. working women 56.66%). Mild (60.53%), moderate (28.95%), and moderately severe anxiety was common among women (total 34/38, 89.47%). Among homemakers, nine had no anxiety, 13 had mild, six had moderate, and one each had moderately severe and severe anxiety, respectively. Among working women, 13 had no anxiety, ten had mild, five had moderate, and two had moderately severe anxiety. Anxiety was less among working women and of milder degree in younger working women, when present. Moderately severe and severe level of anxiety were not reported in younger women in both groups. Homemakers, particularly older women experienced mild anxiety to a greater extent; both working and non-working older women experienced moderate and moderately severe anxiety in equal proportions. Conclusion: Mild and moderate anxiety is more common among women; homemakers, particularly older women are at a high risk.